Hochburg der Sunden - Lauterbach, Thomas (Germany : INDI FILM GmbH ; SWR, 2008)
Aysel is a religious Muslim who for many years has led a sheltered life as a housewife and mother in the provincial south of Germany. When she learns that the state theatre in Stuttgart is looking for non-professional actresses for the tragedy "Medea", she sees an opportunity to escape from her tedious everyday existence – and so she auditions for a part. What initially sounds like a little bit of change in Aysel's life soon proves to be a hard challenge to her view of the world.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films